If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -4) = 28 + 4c Reorder the terms: 4(-4 + x) = 28 + 4c (-4 * 4 + x * 4) = 28 + 4c (-16 + 4x) = 28 + 4c Solving -16 + 4x = 28 + 4c Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 4x = 28 + 16 + 4c Combine like terms: -16 + 16 = 0 0 + 4x = 28 + 16 + 4c 4x = 28 + 16 + 4c Combine like terms: 28 + 16 = 44 4x = 44 + 4c Divide each side by '4'. x = 11 + c Simplifying x = 11 + c
| 1/x^2-1=0 | | 3x-2(7x-9)=70 | | 9(t-6)6+5t=7(2t+3)-10 | | 39/b=13/15 | | -2x=-4+2x | | 11(7+b)=-33 | | 960/4 | | 960/4 | | 7xsquared=-12 | | 0=-5/3x-9 | | 2/2f | | (x^2+7x+12)x+5=y | | 5/36.25=8 | | 4x-y+1=180 | | 5-1/2z=3/4 | | -19+9= | | 64+32+a=180 | | 6.89p+x=5 | | 1/3x+2=3/4 | | x/-12=-3 | | x^3+5x^2+10x=2 | | 3(4x-4)=(12x-1) | | 9=2y+3(y+8) | | 1/x2-1=0 | | x/y=8 | | 15/(2/3) | | 0.14x+29.95=.39x+4.95 | | 3x=-y-t | | 90+5f+2+122=180 | | 6(n+7)=7n-4 | | 4x^2-15x=-3x^2-2x-6 | | 8x+22y=10 |